Karakteristik LVL Lengkung dengan Proses Kempa Dingin Characteristic of LVL Bent by Cold Press Process - Teguh Darmawan; Wahyu Dwianto; Yusup Amin; Kurnia Wiji Prasetyo; Bambang Subiyanto (Masyarakat Peneliti Kayu Indonesia, 2009)
Bending LVL (Laminated Veneer Lumber) is a more effisien method to manufacture bent wood components compare to other methods in raw materials point of view. The Bending LVL was made from Sengon veneers by cold press process with variation of Water Based Polymer-Isocyanate adhesive of 250, 280, 310 g/m2 and bend radius of 200,300, 400 mm. The results showed that the physical properties of Bending LVL made by using Water Based Polymer-Isocyanate adhesive and cold press process was fit with JAS 1639/1986 standard. The optimum adhesive concentration and bend radius was 250 g/m2 and 20 cm, respectively